Akhlak Santri antara Teks dan Konteks - Samidi khalim (Analisa: Journal of Social Science and Religion, 2009)
Moral books tought at Pondok Pesantren Sarang are one of foundations to maintainsalafi tradition and moral of the student at tradisional Muslim School (santri). Thisresearch tries to reveal Tanbihu al Muta’allim book contained moral or duties whichshould be fullfilled by the students in learning at Pondok Pesantren Al Anwar SarangRembang. Critical discourse analyzes is used in this research of Tanbihu al Muta’allimbook. Pondok Pesantren Al Anwar as a educational organization has vision to builda pesantren with their graduates who could understand and comprehend religiousscience, have faith in and godfearing of Allah SWT, are virtuous, have a good moral.Hence, lessons from the teachers or masyayikh coming from yellow book become theirguidance. Santri’s moral in communing with other students, ustadz (teacher) or kyai(religious leader) and also to the community could be understood from those resources,such as Tanbuhu al Muta’allim book.Key Words: Morals, Santri, Book ( Kitab )